Pengaruh Model Project Based Learning (PjBL) Terhadap Hasil Belajar Membuat Gambar Objek Tiga Dimensi Bagi Peserta Didik Kelas IV Sekolah Dasar Gugus 2 Kecamatan Baso (Indo-MathEdu Intellectuals Journal, 2024)
This research is based on the low learning outcomes of students because educators have not used the right learning models and media, learning is still centered on educators, educators dominate learning activities, so that students are less involved in finding contextual problems that are being studied. This study aims to determine the effect of the Project Based Learning (PJBL) model on the learning outcomes of making three-dimensional object drawings for Grade IV students of Elementary School Group 2, Baso District. The type of research used is quasi-experimental design. The design used is Non-equivalent Control Group Design. Cluster random sampling technique. Class IV of SDN 15 Simarasok was designated as an experimental class and class IV of SDN 24 Sungai Cubadak as a control class. The instrument used in this study is a written test in the form of an objective test. The data analysis technique used in this study is a t-test (Paired Simple t-test) with the results of ttable > t-calculation which is 11.517 > 2.048 with a sig (2-tailed) < α 0.05 meaning that H1 is accepted and H0 is rejected So it can be concluded that there is an influence of the Project Based Learning (PBL) model assisted by wordwall media on the learning outcomes of making three-dimensional object images of students in grade IV SDN 15 Simarasok, Baso District.